farmer co-produced actionable agro-climate information services - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
ACIS proven to work with/without seasonal forecasts from official met-offices, with modelling dissemination, sms, online. Now being tested in the context of community disaster planning (Myanmar, see link below)